Research on Refracturing Technology of Horizontal Wells Based on Dynamic Drainage Volume - Dong, Qi; Li, Jianshan; Yang, Lian; Wang, Fei; Zhao, Kun; Huo, Fei (Frontiers in Energy Research, 2022)
Refracturing is an important method to improve the productivity of low-yield and low-efficiency horizontal wells. Due to the influence of geological factors and primary fracturing, it is of great importance to select suitable candidate wells and determine reasonable refracturing timing. Considering that production and pressure are the first-hand data available in the fields, they can be used to evaluate the dynamic drainage volume of fractured horizontal wells and to predict refracturing timing combined with fracturing parameters. In this study, the stimulation potential of refracturing is evaluated by introducing the dynamic drainage volume, and the refracturing timing discrimination model is established. Based on this model, the refracturing timing charts of different initial fracturing scales are drawn. In addition, the reservoir numerical simulation method is used to optimize the method of horizontal well refracturing. The results show that it is advisable to repeat fracturing when the change rate of dynamic drainage volume growth rate is less than 10%. The refracturing methods of restoring the conductivity of fractures or sealing the original fractures and refracturing the new fractures have good development effects. The research is of great significance to the design of horizontal well refracturing.